2015
DOI: 10.1038/srep11029
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctanoic acid exposure for 28 days affects glucose homeostasis and induces insulin hypersensitivity in mice

Abstract: Perfluoroalkyl acids (PFAAs) are widely used in many applications due to their unique physical and chemical characteristics. Because of the increasing prevalence of metabolic syndromes, including obesity, dyslipidemia and insulin resistance, concern has arisen about the roles of environmental pollutants in such diseases. Earlier epidemiologic studies showed a potential association between perfluorooctanoic acid (PFOA) and glucose metabolism, but how PFOA influences glucose homeostasis is still unknown. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 46 publications
2
51
2
Order By: Relevance
“…This finding is supported by two animal studies showing developmental PFOS exposure may link to impaired glucose metabolism in adulthood (Lv et al, 2013;Wan et al, 2014). Moreover, the observed potential protective effect of PFOA in our study is consistent with a recent animal study, which demonstrated that PFOA may induce insulin hypersensitivity in mice (Yan et al, 2015). The discrepancy between our finding and the results from prior studies may be due to different sampling procedures, different criteria used to define diabetes, and different exposure levels of PFASs.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This finding is supported by two animal studies showing developmental PFOS exposure may link to impaired glucose metabolism in adulthood (Lv et al, 2013;Wan et al, 2014). Moreover, the observed potential protective effect of PFOA in our study is consistent with a recent animal study, which demonstrated that PFOA may induce insulin hypersensitivity in mice (Yan et al, 2015). The discrepancy between our finding and the results from prior studies may be due to different sampling procedures, different criteria used to define diabetes, and different exposure levels of PFASs.…”
Section: Discussionsupporting
confidence: 76%
“…However, PPAR-independent mechanisms may play an important role in glucose metabolism. For instance, PFOA has been shown to activate serine/threonine protein kinase (AKT) pathway along with the loss of the phosphatase and tensin homolog (PTEN) expression and subsequently to enhance insulin sensitivity and inhibit hepatic glycogen synthesis (Yan et al, 2015). On the other hand, there may also be PPAR-independent mechanisms for PFOS-related diabetogenesis although in vitro studies specifically to explore the pathogenic pathways of PFOS on glucose homeostasis are rather scarce.…”
Section: Discussionmentioning
confidence: 98%
“…In rat liver, PFOA exposure has been shown to increase mitochondrial proton conductance (Starkov & Wallace, ). A 28 day exposure to PFOA affected glucose homeostasis in mice (Yan et al ., ). In the present study, the fluorescence lifetime measurements of NADH and FAD coenzymes provide insight into the dynamics of cellular metabolism.…”
Section: Discussionmentioning
confidence: 97%
“…PFOA exhibits structural similarity to fatty acids and has been shown to affect lipid metabolism by acting through the transcription factor peroxisome proliferator-activated receptor (PPAR)-α (Maloney & Waxman, 1999;Rosen et al, 2007;Takacs & Abbott, 2007;Wang et al, 2013). PFOA can induce hepatomegaly and hepatocellular adenomas in rats and it was shown variously to cause weight loss, increase total cholesterol and perturb cellular metabolism, including lipid metabolism, glucose metabolism, oxidative phosphorylation and mitochondrial dysfunction in mice, zebrafish and human systems (Abbott et al, 2012;Hagenaars et al, 2013;Nelson et al, 2010;Peng et al, 2013;Yan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…PFCs have been ubiquitously detected in abiotic and biotic media, including surface and ground water, sediments, aquatic organisms, human blood and breast milk78910. In addition, some PFCs have been found to have acute and subchronic toxicity as peroxisome proliferators, gap junction and intercellular communication inhibitor311121314. Thus, long time exposure to PFCs would pose potential risk to human being and ecosystem1516.…”
mentioning
confidence: 99%